2011
DOI: 10.1038/jcbfm.2010.231
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 2 and 4 in ischemic stroke: Outcome and therapeutic values

Abstract: Stroke triggers an intense inflammatory response that could be a consequence of Toll-like receptors (TLRs) activation. However, the clinical significance and the therapeutic possibilities of TLR in stroke is not completely clear. In this study, we analyze the association between the expression of TLR2 and TLR4, inflammatory molecules and endogenous ligands, and clinical outcome of ischemic stroke patients, and we test the potential of TLR2/TLR4 and their endogenous ligands as therapeutic targets. For this purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 21 publications
2
106
0
3
Order By: Relevance
“…Post-ischemic inflammation and subsequent ischemic damage depend on TLR2 and TLR4, but not TLR9 (Hyakkoku et al 2010), because TLR2-or TLR4-deficiency significantly attenuates ischemic brain damage and suppresses inflammatory cytokine expression in infiltrating immune cells on day 1 after ischemia-reperfusion in mice (Shichita et al 2012). The clinical relevance of TLR2 and TLR4 in stroke patients has been also demonstrated (Brea et al 2011). Despite these findings about the importance of TLR, the mechanisms responsible for activating them in infiltrating immune cells, such as macrophages and T cells, are not yet fully understood.…”
Section: Tlrs As Damps Receptorsmentioning
confidence: 93%
“…Post-ischemic inflammation and subsequent ischemic damage depend on TLR2 and TLR4, but not TLR9 (Hyakkoku et al 2010), because TLR2-or TLR4-deficiency significantly attenuates ischemic brain damage and suppresses inflammatory cytokine expression in infiltrating immune cells on day 1 after ischemia-reperfusion in mice (Shichita et al 2012). The clinical relevance of TLR2 and TLR4 in stroke patients has been also demonstrated (Brea et al 2011). Despite these findings about the importance of TLR, the mechanisms responsible for activating them in infiltrating immune cells, such as macrophages and T cells, are not yet fully understood.…”
Section: Tlrs As Damps Receptorsmentioning
confidence: 93%
“…Some authors have reported improved survival and functional outcome associated with statin treatment, but these findings have not been consistently replicated. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][31][32][33][34][35][36] Interpretations can be difficult because of limited sample sizes in some reports and possible bias in statin allocation in other studies, particularly those in which statins were allocated in a nonrandomized fashion. Some authors have also reported worse outcomes in patients treated with the combination of acute statins and intravenous thrombolysis.…”
mentioning
confidence: 99%
“…A significant role for TLR4 in the pathogenesis of stroke has been reported by several studies [47,48]. There are several animal models for ischemia, and the role of TLR4 in ischemia and stoke has been investigated in these models.…”
Section: Tlr4 and Strokementioning
confidence: 99%